HISTORISITAS POLITIK PEREMPUAN INDONESIA - Jati, Wasisto Raharjo (Paramita: Historical Studies Journal, 2014)
This article aims to analyze historicity of political participation and representation of women in the political landscape in Indonesia. This paper used the perspective of feminism theory as core analysis in reviewing its issue. Periodicity of Indonesian womens political participation is very volatile and depends on the political situation contemporary. Indonesian womens political participation in the era of colonialism experienced domestication, revivalism in the Sukarno era, stigmatization in the New Order era, and is now experiencing ambiguity in the Reformation era. Indonesian womens political participation need to find a strong platform to promote the aspirations of his peopleKeywords: partisipation, representation, domestification, stigmatization, and women politic.Artikel ini bertujuan untuk menganalisis histo-risitas partisipasi politik dan keterwakilan perempuan dalam lanskap politik di Indonesia. Tu-lisan ini menggunakan perspektif teori feminisme sebagai analisis inti dalam meninjau isu nya. Periodisitas partisipasi politik perempuan Indonesia sangat fluktuatif dan tergantung pada situasi politik kontemporer. Partisipasi politik perempuan Indonesia di era kolonialisme mengalami domestikasi, revivalisme di era Soekarno, stigmatisasi di era Orde Baru, dan sekarang mengalami ambiguitas dalam era Reformasi. Partisipasi politik perempuan Indonesia perlu menemukan platform yang kuat untuk memperjuangkan aspirasi rakyatnyaKata kunci: partisipasi, representasi, domestifikasi, stigmasi, politik perempuanÂ Â